An overview of seminar II students’ employability skills and the expected destinations to work: a students’ perspective from the Bachelor of arts in modern Languages with specialization in French and English at the Department of Foreign Languages of the University of El Salvador, year 2015. - Girón Torres, Aarón Christian
This research paper provides the information of the procedure followed and findings of a research study of Modern Languages students’ perceptions of the employability skills developed in their major and the expected destinations to perform those skills. This paper first presents all the parts that compose the Statement of the problem like: the Description of the problem, the General and Specific Objectives that this research intends to reach, the Research Questions, the Delimitation of the problem, and the Justification that refers to the explanation of the purpose of the study, then the report highlights key definitions and information in the Theoretical Framework, concerning the employability skills with particular reference to understand the core of this topic and goes on to present information about the Offshore Business Service Industry in El Salvador that groups the main enterprises offering employment positions for Modern Languages students, and finally, this same part contains information about the up-to-date practices in the area of foreign languages and relevant information about the major in Modern Languages at the University of El Salvador (UES).